Theoretical treatment on externally-seeded superradiance from N2+ in femtosecond laser filamentation in low-pressure nitrogen - Wang, Quanjun; Ding, Pengji; Wilkins, Shane G.; Athanasakis-Kaklamanakis, Michail; Zhang, Yuxuan; Liu, Zuoye; Hu, Bitao (Frontiers in Physics, 2023)
We perform a theoretical investigation of a collective emission in tunnel-ionized nitrogen molecules triggered by a coherent seed pulse. A semiclassical theory of superradiance that includes the superradiant temporal profile, characteristic duration, time delay, intensity is achieved. The theoretical predictions of 391-nm forward emission corresponding to the transition between $\mathrm{N_2^+}(B^2\Sigma_u^+,\nu'=0)$ and $\mathrm{N_2^+}(X^2\Sigma_g^+,\nu=0)$ as a function of nitrogen gas pressure are compared with the recent experimental data [Ding P. \textit{Lasing effect in femtosecond filaments in air}, Ph.D. thesis, Universit´e Paris-Saclay (2016)]. The good agreement demonstrates that the time-delayed optical amplification inside the molecular nitrogen ions is superradiance.